2019
DOI: 10.1039/c9nr06774d
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2-targeted superparamagnetic Fe3O4-PEG-G5-MMP2@Ce6 nanoprobes for dual-mode imaging and photodynamic therapy

Abstract: A novel matrix metalloproteinase 2-targeted superparamagnetic nanoprobes for MRI, NIR and photodynamic therapy of tumors have been developed. The nanoprobes can significantly inhibit the tumor growth compared with PBS and free Ce6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…The chemicals adopted in our research were from Sigma (MO, USA) unless otherwise stated. The human lung carcinoma cell line (A549) was purchased from ATCC (Virginia, USA) and cultured in Dulbecco's modified eagle medium (Gibco, California, USA) supplied with 10% foetal bovine serum (Gibco, California, USA) under standard conditions as previously reported [19]. Male Balb/c nude mice were purchased from the Model Animal Research Center of Nanjing University (Nanjing, China) and raised in standard specific pathogen free (SPF) condition with sufficient food supply.…”
Section: Methodsmentioning
confidence: 99%
“…The chemicals adopted in our research were from Sigma (MO, USA) unless otherwise stated. The human lung carcinoma cell line (A549) was purchased from ATCC (Virginia, USA) and cultured in Dulbecco's modified eagle medium (Gibco, California, USA) supplied with 10% foetal bovine serum (Gibco, California, USA) under standard conditions as previously reported [19]. Male Balb/c nude mice were purchased from the Model Animal Research Center of Nanjing University (Nanjing, China) and raised in standard specific pathogen free (SPF) condition with sufficient food supply.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in vivo results not only confirmed that it can act as a dual‐mode imaging probe for tumor diagnosis but also demonstrated that it could effectively suppress tumor growth (Figure 2b,c). [ 48 ] Charge‐switchable polymers are a kind of smart organic ligand that can switch its charge from negative or neutral to positive in response to a specific stimulus when it is used in different biological environments. [ 49 ] Thus, MNPs could be modified with charge‐convertible polymers to endow this nanohybrid with a unique charge‐convertible property for enhanced tumor targeting and cellular uptake.…”
Section: Functionalization Of Mnps With Organic Ligands In the Biomedical Fieldmentioning
confidence: 99%
“…The generated magnetitepoly(g-benzyl-L-glutamate) (PBLG) nanoparticles were further Reproduced with permission. [48] Copyright 2019, Royal Society of Chemistry.…”
Section: Surface-growth Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26] Likewise, NIR imaging with real-time behavior, noninvasiveness and high sensitivity has been developed for disease diagnosis. [27][28][29][30][31][32][33][34][35][36] However, its shortcomings, such as shallow tissue penetration depth, low spatial resolution and rapid, limit its clinical application. [37][38][39][40][41][42][43] Fortunately, PA imaging perfectly overcomes these problems.…”
Section: Introductionmentioning
confidence: 99%